Companionship and bullying in nursing students at DICIVA (Jóvenes en la Ciencia, 2024)
School violence is not a simple social fact, but a complex and multi-referential phenomenon, that is, it refers to the possibility of knowing reality from different perspectives, taking into account the environment, person and personal aspects of experience and development of both the aggressor as well as the victim. Objective: Compare the level of presence or absence of camaraderie and rivalry between students in the sixth and eighth semester of the Nursing program at Diciva. Descriptive cross-sectional study, a sample of 21 students was used at convenience, where informed consent was mentioned. The sociometric and bullying questionnaires were applied. It was shown that nursing students have a positive school coexistence among themselves, that is, they have a solid intergroup relationship where the majority support and respect each other. These results suggest the presence of camaraderie and the absence of bullying in sixth and eighth semester nursing students.